2006
DOI: 10.1118/1.2170616
|View full text |Cite
|
Sign up to set email alerts
|

A semianalytic model to extract differential linear scattering coefficients of breast tissue from energy dispersive x‐ray diffraction measurements

Abstract: The goal of this work is to develop a technique to measure the x-ray diffraction signals of breast biopsy specimens. A biomedical x-ray diffraction technology capable of measuring such signals may prove to be of diagnostic use to the medical field. Energy dispersive x-ray diffraction measurements coupled with a semianalytical model were used to extract the differential linear scattering coefficients [mus(x)] of breast tissues on absolute scales. The coefficients describe the probabilities of scatter events occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 64 publications
1
32
1
Order By: Relevance
“…In Fig. 3(a), both measured data by Kidane et al 41 and LeClair et al 37 matched well with the data calculated using Poletti et al 40 F and Hubbell et al 52 S values. Figure 3(b) shows data for fibroglandular tissue.…”
Section: Scatter Cross Sectionssupporting
confidence: 76%
See 1 more Smart Citation
“…In Fig. 3(a), both measured data by Kidane et al 41 and LeClair et al 37 matched well with the data calculated using Poletti et al 40 F and Hubbell et al 52 S values. Figure 3(b) shows data for fibroglandular tissue.…”
Section: Scatter Cross Sectionssupporting
confidence: 76%
“…Although in previous work, 37,42,43 the symbol used for dμ s ∕dΩ was simply μ s , the new notation is more appropriate for denoting a differential linear scattering coefficient. At low x, it is F, which provides most contrast between tissue types but both types of scatter were included in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Although several authors (Kidane et al, 1999;Castro et al, 2004;Geraki et al 2004;LeClair et al, 2006;Ryan and Farquharson, 2007;Oliveira et al, 2008) have proved that a different diffraction signal is achieved from normal and neoplastic breast tissue in the momentum transfer range 0.5 -4 nm -1 , there are few data about identification of different lesion types. In this study, the diffraction patterns of different lesions have been investigated using EDXRDCT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, based both on the SAXS (Lewis et al, 2000;Fernandez et al, 2002;Round et al, 2005;Suhonen et al, 2005;Sidhu et al, 2009) and on the XRD modality (Kidane et al, 1999;Poletti et al, 2002;LeClair et al, 2006;Ryan and Farquharson, 2007;Oliveira et al, 2008), have shown the feasibility of breast tissue characterization. Of particular interest is the possibility of discriminating healthy and neoplastic tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation